Quality Control Model In The Sustainable Coconut Sugar Supply Chain (Case Study: SMEs In Indragiri Hilir District, Riau) - Wardah, Siti; Wulandari, Feni; Amin, Muhammad (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Ant-sugar SMEs are developing in the Indragiri Hilir Regency. This industry uses the sap of hybrid coconut trees to make sugar. To maintain sustainability, SMEs require assistance with quality from upstream to downstream. Based on this, the research attempts to ascertain the mechanism of the sugar supply chain, identify the elements that lead to flaws, and suggest ways to enhance the chain's quality. Identify supply chain conditions using the Vorst method and identify the root causes of problems using the FTA method and quality improvement proposals based on evaluating potential failure levels using the FMEA method. The research results show that the supply chain members are Farmers, SMEs and Final Consumers. The factors causing defects in coconut sap water and ant sugar are human and environmental. The proposed improvement at the farmer level is that the cracked wood preservative must be measured correctly before taking coconut sap water. In contrast, at the SME level, workers pay attention to the ongoing production process and carry out periodic checks when boiling the sap water so that the maturity level is perfect and stir optimally so as not to cause failure. In the crystallization of ant sugar.